The Future of Islet Transplantation Is Now - Bottino, Rita; Knoll, Michael F.; Knoll, Carmela A.; Bertera, Suzanne; Trucco, Massimo M. (Frontiers in Medicine, 2018)
Milestones in the history of diabetes therapy include the discovery of insulin and successful methods of beta cell replacement including whole pancreas and islet cell transplantation options. While pancreas transplantation remains the gold standard for patients who have difficulty controlling their symptoms with exogenous insulin, islet allotransplantation is now able to provide similar results with some advantages that make it an attractive potential alternative. The Edmonton Protocol, which incorporated a large dose of islets from multiple donors with steroid-free immunosuppression helped to establish the modern era of islet transplantation almost 20 years ago. While islet allotransplantation is recognized around the world as a powerful clinical therapy for type 1 diabetes it is not yet recognized by the Federal Drug Administration of the United States. Large-scale clinical trials administered by the Clinical Islet Transplantation Consortium have recently demonstrated that the well-regulated manufacture of a human islet product transplanted into patients with difficult to control type 1 diabetes and with a history of severe hyperglycemic episodes can safely and efficaciously maintain glycemic balance and eliminate the most severe complications associated with diabetes. The results of these clinical trials have established a strong basis for licensure of clinical islet allotransplantation in the United States. Recognition by the Federal Drug Administration would likely lead to third party reimbursement for islet allotransplantation as a therapeutic option in the United States and would make the treatment available to many more patients. The high costs of rampant diabetes justify the expense of the treatment, which is in-line with the costs of clinical pancreas transplantation. While much enthusiasm and hope is raised towards the development and optimization of stem cell therapy, the islet transplantation community should push towards licensure, if that means broader access of this procedure to patients who may benefit from it. Even as we prepare to take the first steps in that direction, we must acknowledge the new challenges that a shift from the experimental to clinical will bring. Clinical islet allotransplantation in the United States would be a game-changing event in the treatment of type 1 diabetes and also generate enthusiasm for continued research.